Stereoselective Approaches toward the Synthesis of Nucleoside Antibiotic Core Aminoribosyl Glycyluridine. Issue 35 (10th July 2019) - Patel, Bhautikkumar; Grant, Gary; Zunk, Matthew; Rudrawar, Santosh
Abstract : Antibiotics that have a novel mechanism of action are urgently required for treatment of drug‐resistant microorganisms. Naturally occurring nucleoside antibiotics have shown promising antibacterial activity by inhibiting bacterial translocase MraY, a key enzyme involved in catalysis of the first step of bacterial peptidoglycan biosynthesis. Despite having promising antibiotic properties, a major challenge toward development of this important class of compounds as drug candidates is their complex multistep synthesis. Specifically, efficient synthetic methodologies toward producing the aminoribosylated uridine‐derived core unit in a stereo‐controlled manner is seen as an essential prerequisite for detailed structure‐activity relationship (SAR) studies. This review summarizes approaches available for the stereoselective synthesis of nucleoside core pharmacophores, including both 5′‐ C ‐glycyluridine (GlyU) as well as it's β‐selective ribosylation. Abstract : Nucleoside antibiotics are promising lead structures for development of novel antibacterial agents. They have shown broad spectrum antibiotic property via inhibition of novel enzyme MraY (translocase I). This minireview summarizes approaches reported for the stereoselective synthesis of nucleoside core aminoribosyl glycyluridine structure, which includes two topics: 1) Stereo‐controlled synthesis of the ribosyl acceptor (5′‐ C ‐glycyluridine) 2) β‐selective ribosylation of the ribosyl acceptor (5′‐ C ‐glycyluridine).